2015
DOI: 10.1039/c4ra16138f
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient loading of doxorubicin in Prussian Blue nanocages for combined photothermal/chemotherapy against hepatocellular carcinoma

Abstract: Doxorubicin-loaded Prussian Blue-based nanoparticles for combined photothermal/chemotherapy against hepatocellular carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 36 publications
0
46
0
1
Order By: Relevance
“…97 Over the past two decades, MOFs have been applied in photonics, 98 catalysis, [99][100][101] biosensors, 102,103 gas storage, [104][105][106][107] and drug delivery. [108][109][110][111] For drug delivery, the high drug-loading capacity of MOFs relies largely on three factors: 1) high surface area (3,100-5,900 m 2 /g) 108 and large, regular, accessible cages and tunnels; 2) good physicochemical stability in circulation and quick stimuli 109,113 -effectively in hexane solution. X-ray powder diffraction and N 2 -adsorption experiments showed that both MOFs retained their excellent crystalline structures, and almost all the cages and tunnels were filled and/or blocked by the drug molecules.…”
Section: Absorption/desorption-type Mofs As Carriersmentioning
confidence: 99%
“…97 Over the past two decades, MOFs have been applied in photonics, 98 catalysis, [99][100][101] biosensors, 102,103 gas storage, [104][105][106][107] and drug delivery. [108][109][110][111] For drug delivery, the high drug-loading capacity of MOFs relies largely on three factors: 1) high surface area (3,100-5,900 m 2 /g) 108 and large, regular, accessible cages and tunnels; 2) good physicochemical stability in circulation and quick stimuli 109,113 -effectively in hexane solution. X-ray powder diffraction and N 2 -adsorption experiments showed that both MOFs retained their excellent crystalline structures, and almost all the cages and tunnels were filled and/or blocked by the drug molecules.…”
Section: Absorption/desorption-type Mofs As Carriersmentioning
confidence: 99%
“…Compared with other inorganic PTT agents including carbon-based nanomaterials [5][6][7][8][9] , noble metal-based nanostructures [10][11][12][13][14][15] , as well as transition-metal sulfides and oxides [16][17][18][19] , which in general are not biodegradable and thus have tremendous difficulties in terms of clinical translation, PB is already a clinically approved agent and can be obtained with low costs. Therefore, many groups including ours have explored the applications of PB-based nanoagents as PTT agent for cancer treatment in animal models [20][21][22][23][24][25][26][27][28] . Further, it has been found that doping of other paramagnetic ions, such as Gd 3+ and Mn 2+ into PB could enhance its T1 contrasting ability in magnetic resonance (MR) imaging [29][30][31][32][33][34] For in vitro cell toxicity assay, 4T1 cells were seeded in 96-well plates at a density of 10 4 Bio-RAD) to determine their relative cell viability.…”
Section: Introductionmentioning
confidence: 99%
“…24 Meanwhile, PB-based nanostructures exhibit strong optical absorbance in NIR region, high photothermal conversion efficiency and superior photothermal stability, which also make them an extraordinary photothermal agent for PTT. [25][26][27][28][29][30][31] In addition, synthesis of PBbased nanoparticles (NPs) is cost-effective based on a simple and facile reaction between FeCl3 and K4[Fe(CN)6] in acidic condition. 32 Because the cellular uptake efficiency of ultrasmall PB NPs is considerably high, it has a good potential as a nonviral vector for efficient gene delivery 29 .…”
Section: Introductionmentioning
confidence: 99%